2019
DOI: 10.1002/lno.11149
|View full text |Cite
|
Sign up to set email alerts
|

How effective are tidal marshes as nature‐based shoreline protection throughout seasons?

Abstract: Nature-based mitigation is increasingly proposed as a strategy to cope with global change and related risks for coastal flooding and erosion. Tidal marshes are known to provide shoreline protection as their aboveground biomass attenuates waves and their belowground biomass contributes to reducing erosion rates. The aim of this study was to quantify how effectively wave attenuation rates and erosion reduction rates are sustained throughout seasons in pioneer tidal marshes in the Elbe estuary (Germany). Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…The 750 m width of the marsh is still sufficient to cope with recession. While direct dampening by stems was not included in this study, this agrees with many observations that most waves break at the edge of the marsh and further dampen decays landward [10,45,46]. According to Möller et al [10], a width of 40 m is sufficient to already reduce 15% of an incoming wave's height.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The 750 m width of the marsh is still sufficient to cope with recession. While direct dampening by stems was not included in this study, this agrees with many observations that most waves break at the edge of the marsh and further dampen decays landward [10,45,46]. According to Möller et al [10], a width of 40 m is sufficient to already reduce 15% of an incoming wave's height.…”
Section: Discussionsupporting
confidence: 82%
“…The attenuation of waves by a marsh is one of the benefits for flood protection. Many studies have found significant wave height reductions within the first 10s of metres of marsh [10,16,[43][44][45]. Waves are dampened further with distance travelled across the marsh.…”
Section: Flood Protection Services By Marshesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant issues in coastal dune management are related to the mitigation of negative impacts during and consequences after unusual storms and floods with different origins [8]. The holistic approach of integrated coastal zone management recommends nature-based mitigation strategies based on the replacement of artificial coastal protection and stabilization structures with dunes stabilized with plants [12,14]. Natural dune vegetation reduces wind velocity, and with its extensive system of horizontal and vertical rhizomes, holds a large amounts of trapped sand that absorbs wave energy [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the coastal areas lose their buffering function permanently or till the recovery of plant communities of dominant sand stabilizers, mostly within one vegetation season (Figure 1b). dunes stabilized with plants [12,14]. Natural dune vegetation reduces wind velocity, and with its extensive system of horizontal and vertical rhizomes, holds a large amounts of trapped sand that absorbs wave energy [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%